DIFFICULTIES OF ELEMENTARY SCHOOL STUDENTS IN PRODUCTIVE SKILL - Yuyun Yulia (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2010)
This paper aims at describing students’ difficulties in spoken utterances. To achieve the objective, the research site is some schools in Yogyakarta Special Province, both public and private schools. The reason to choose is first, the schools provide English from the very beginning level, that is the first grade of elementary school, second, the teachers are from English educational background and third, the schools get A for the accreditation. Observation and interview techniques are employed to collect data. The results reveal that English teachers tend to teach form and vocabularies. As a result, a complete text in a form of dialogue or a descriptive text is still difficult to reach. The students perform uncontextual and uncomplete text. The text is not a monologue or dialogue, a short functional text, or a descriptive text as suggested by the curriculum. Most utterances are in a form of words, phrases and sentences; the text produced is sentence copying from textbooks or from teachers. The teaching learning process then is divided into three steps of teaching, namely pre-teaching, while-teaching, and post-teaching. Of the three steps of teaching, English teachers tend to be teachers centered teaching and the focus is still on vocabularies and English rules. They teach about the language. They speak more in Bahasa Indonesia starting from pre-teaching up to post teaching. The tasks given are on vocabulary and forms. As the result of teachers’ teaching then it affects on students’ performance. The students are in doubt even do not know how to communicate or perform a simple dialogue among friends in English. It contrasts to the aim of English learning for children, that is performative level. They actually should be trained more on formulaic expressions rather than on rules. In brief, to be an English teacher for elementary level needs to have good ability in English classroom instructions, be a grammar sensitive teacher and be a creative teacher in conducting teaching learning process.